PENENTUAN SEKTOR EKONOMI UNGGULAN DAN PENGEMBANGAN SUB SEKTOR UNGGULAN PERTANIAN TERHADAP KETAHANAN EKONOMI DAERAH DI KABUPATEN KONAWE SULAWESI TENGGARA - Leni Saleh (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2015)
This research is focused to determine the regional leading sector in the sub regional economy and the agricultural sector of Konawe Regency as the information and considerations in planning economic development. Secondary data such as time series of the Gross Regional Domestic Product (GRDP) of Konawe Regency and Southeast Sulawasi province in the period 2006-2009 are applied. Klassen Typology, Location Quotient (LQ), and Shift Share are tools of analysis. Location Quotient analysis results show the economic sectors of agriculture, the sector building/construction, electricity, gas and water utilities, as well as the services sector is a sector on the basis Konawe. While the Location Quotient analysis results indicate that the sub sectors of agriculture sub sector food crops and livestock sub-sector is the sector on the basis Konawe. Shift Share analysis results show that most high-growth sectors are agriculture, the sector while the lowest growth rate is the electricity, gas and water supply. The analysis showed Klassen Tipology the prime sector, namely agriculture, construction sector and services sector. Local development planning should be based on development priorities leading sectors by taking into account non-leading sectors with emphasis on development in the advanced sectors of the economy and growing rapidly, and the potential to provide a beneficial impact for the development of other sectors that have a role in realizing Konawe regional economic resilience of the national security implications for the region .